Naskh and Mansukh in Contemporary Islamic Exegetical Thought: Reconstructing the Paradigm through the al-Jam’u wa al-Tawfīq Approach - Suriyadi Suriyadi; Fathorrahman Fathorrahman (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to reconstruct the paradigm of naskh and mansukh in contemporary islamic exegetical thought by positioning the al-jam’u wa al-tawfīq approach as the primary methodological framework for resolving apparent contradictions among qur'anic verses. The research employs a qualitative library research design, drawing upon classical works of Ulum Al-Qur’an, uṣul al-fiqh, and tafsīr, alongside contemporary scholarly literature on qur'anic hermeneutics, maqasid al-shari’ah, and modern islamic legal thought. Data were collected through systematic documentation of authoritative sources and analyzed using qualitative content analysis, comparative analysis, and conceptual synthesis to examine the methodological evolution of naskh from classical to contemporary scholarship. The findings reveal a significant epistemological shift from viewing naskh as the primary mechanism for resolving legal differences toward prioritizing al-jam’u wa al-tawfīq, historical contextualization, and maqasid al-shari’ah before recognizing the occurrence of abrogation. The study demonstrates that many cases traditionally classified as mansukh can be more appropriately understood through harmonization, contextual differentiation, and gradual legislation (tadarruj fi al-tashrīʿ). The novelty of this study lies in the formulation of an integrated theoretical framework that systematically combines al-jam’u wa al-tawfīq, maqasid al-shari’ah, historical contextualization, and gradual legislation into a unified epistemological model, repositioning naskh as a valid but highly restricted interpretative mechanism while reinforcing the coherence, universality, and contemporary relevance of the qur'an in islamic exegetical thought and islamic education.